Comparison of the difference in the anti-inflammatory activity of two different color types of Farfarae Flos based on in vitro, in vivo experiments and untargeted metabolomics - Zhou, Kexin; Peng, Liang; Jing, Yiyao; Luo, Yao; Yan, Yonggang; Zhang, Gang; Guo, Qi; Yang, Bingyue (Frontiers in Pharmacology, 2024)
Due to its remarkable anti-inflammatory pharmacological activity, Farfarae Flos has gained extensive usage in the treatment of various inflammatory diseases such as bronchitis, pneumonia, prostatitis and colitis. And Farfarae Flos come in two color types depending on the color of the flowers: yellowish-white (YW), and purplish-red (PR). However, the difference in anti-inflammatory activity and metabolic profiles between the two flower colors remains unexplored. This study aims to explore the difference in the anti-inflammatory potential between YW and PR variants of Farfarae Flos and unravel the mechanisms responsible for the observed differences in anti-inflammatory activity through an integrated approach encompassing untargeted metabolomics and in vivo/vitro experimental studies. Initially, we verified the contrasting effects of YW and PR on the inhibition of the inflammatory factors interleukin-6 (IL-6) and nitric oxide (NO) by utilizing an in vitro RAW 264.7 cell inflammation model. Subsequently, a comprehensive evaluation of the systemic inhibitory capacity of YW and PR on IL-6, Interleukin-10 (IL-10), and tumor necrosis factor-α (TNF-α) was conducted using a validated whole-body mouse model, followed by the analysis of inflammatory factors and histological examination of collected serum, liver, and spleen after 7 days. Furthermore, non-targeted metabolomics profiling was employed to analyze the metabolite profiles of Farfarae Flos with different colors, and quantitative analysis was conducted to identify differential metabolites between YW and PR. The correlation between the anti-inflammatory activities of differentially accumulated metabolites (DAMs) and Farfarae Flos was investigated, resulting in the identification of 48 compounds exhibiting significant anti-inflammatory activity.Additionally, KEGG pathway enrichment analysis was performed to elucidate the underlying mechanisms. Our findings demonstrate that both YW and PR possess anti-inflammatory abilities, with PR exhibiting significantly superior efficacy. The integration of in vivo/vitro experiments and non-targeted metabolomics confirmed the exceptional anti-inflammatory potential of PR and solidified its classification as the 'purplish-red better' of Farfarae Flos.This study provides valuable insights into the breeding and medical transformation of Farfarae Flos varieties, along with a scientific basis for the establishment of quality standards and the development of new drugs utilizing Farfarae Flos.